Functionally relevant coupled dynamic profile of bacteriorhodopsin and lipids in purple membranes. - Kamihira, M; Watts, A (2006)
The dynamics of bacteriorhodopsin (bR) and the lipid headgroups in oriented purple membranes (PMs) was determined at various temperatures and relative humidity (rh) using solid-state NMR spectroscopy. The 31P NMR spectra of the alpha- and gamma-phosphate groups in methyl phosphatidylglycerophosphate (PGP-Me), which is the major phospholipid in the PM, changed sensitively with hydration levels. Between 253 and 233 K, the signals from a fully hydrated sample became broadened similarly to those of a dry sample at 293 K. The 15N cross polarization (CP) NMR spectral intensities from [15N]Gly bR incorporated into fully hydrated PMs were suppressed in 15N CP NMR spectra at 293 K compared with those of dry membranes but gradually recovered at low temperatures or at lower hydration (75%) levels. The suppression of the NMR signals, which is due to interference with proton decoupling frequency (approximately 45 kHz), coupled with short spin-spin relaxation times (T2) indicates that the loops of bR, in particular, have motional components around this frequency. The motion of the transmembrane alpha-helices in bR was largely affected by the freezing of excess water at low temperatures. While between 253 and 233 K, where a dynamic phase transition-like change was observed in the 31P NMR spectra for the phosphate lipid headgroups, the molecular motion of the loops and the C- and N-termini slowed, suggesting lipid-loop interactions, although protein-protein interactions between stacks cannot be excluded. The results of T2 measurements of dry samples, which do not have proton pumping activity, were similar to those for fully hydrated samples below 213 K where the M-intermediates can be trapped. These results suggest that motions in the 10s micros correlation regime may be functionally important for the photocycle of bR, and protein-lipid interactions are motionally coupled in this dynamic regime.